Determining The Right Market Segmentation and Marketing Tactic to Increase Sales at Teguk Indonesia - Muhamad Catur Gunandi; Ira fachira (Eduvest - Journal of Universal Studies, 2025)
This research aims to determine the existence of a piece rate payment scheme that has an impact on the non-receipt of pocket money rights for remote internship participants, which should be obtained based on Indonesian Labor Law. This legal research is conducted with a doctrinal type research method that presents a systematic explanation of regulations, synchronization between laws and regulations and policy analysis in a prescriptive analytical manner to provide coherence truth. The results show that the Piece Rate Payment scheme has the potential to deprive remote internship participants of their rights in terms of pocket money. This is because the payment of pocket money will not be fulfilled by the company if the intern does not meet a certain target based on the internship contract. In addition, because Law No. 13 of 2003 concerning Manpower and Regulation of the Minister of Manpower and Transmigration No. PER.08/MEN/V/2008 concerning Procedures for Licensing and Implementation of Overseas Apprenticeship, do not regulate the allowance payment scheme. So, the economic protection efforts that can be done are by providing provisions in the relevant regulations regarding the company's obligation to provide a non-target-based allowance scheme, as well as supervision of overseas apprenticeship providers.